1982
DOI: 10.1093/jat/6.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Urine Disposition of 1- -Acetylmethadol and its Principal Metabolites in Man

Abstract: The disposition of 1-alpha-acetylmethadol (LAAM) in plasma and urine was monitored by GC/CIMS following oral administration of 10 doses (0.73-1.5 mg/kg) over 42 days, to twelve human subjects. Plasma concentration-time course profiles fitted a two-compartment, first order kinetic model. Mean plasma t1/2 alpha for LAAM was 2.4 hours; t1/2 beta was 37.5 hours for the first dose and 46.8 hours for the last dose. The mean terminal half-life for nor-LAAM was 38.2 hours for first and 64.6 for last dose; for dinor-LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…First, the t max of 3.9 hours observed for dinorLAAM in this study is much shorter than that noted previously (16‐31 hours) 21 , 22 . Second, the C max and AUC for LAAM in this study are lower than expected solely on the basis of dose differences when compared with those previously observed by Finkle et al, 21 Henderson et al, 20 and Walsh et al 22 When the dose difference is eliminated by calculating an apparent oral clearance, respective values of 37.6, 12.4, and 10.5 min/mL at doses of 5, 20, and 40 mg/70 kg are yielded. At the low dose used in our study, at which saturation effects would not be expected, it is hypothesized that much more LAAM and norLAAM may be metabolized during first‐pass metabolism, and this would account for the lower‐than‐expected C max and AUC of LAAM.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…First, the t max of 3.9 hours observed for dinorLAAM in this study is much shorter than that noted previously (16‐31 hours) 21 , 22 . Second, the C max and AUC for LAAM in this study are lower than expected solely on the basis of dose differences when compared with those previously observed by Finkle et al, 21 Henderson et al, 20 and Walsh et al 22 When the dose difference is eliminated by calculating an apparent oral clearance, respective values of 37.6, 12.4, and 10.5 min/mL at doses of 5, 20, and 40 mg/70 kg are yielded. At the low dose used in our study, at which saturation effects would not be expected, it is hypothesized that much more LAAM and norLAAM may be metabolized during first‐pass metabolism, and this would account for the lower‐than‐expected C max and AUC of LAAM.…”
Section: Discussioncontrasting
confidence: 65%
“…The increased AUC of dinorLAAM is not as readily explained. Other metabolites of LAAM, the methadols and ring hydroxylation products, have been described in experimental animals and humans, 21 , 30 , 31 and Oda and Kharasch 17 and Huang et al 26 have shown that norLAAM and dinorLAAM formation does not account for all of the LAAM utilization in human liver microsomes and complementary deoxyribonucleic acid–expressed CYPs, respectively. Inhibition of an alternative pathway of metabolism may explain the increased dinorLAAM AUC and may have contributed to the increased norLAAM AUC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous pharmacokinetic studies on LAAM have been conducted in subjects who were opioid tolerant. They were either receiving maintenance doses of LAAM,21,29,30 or were active, but nonaddicted, users of heroin 23. The current findings represent the first for subjects who are opioid‐naive.…”
Section: Resultsmentioning
confidence: 99%